THE INFLUENCE OF ISLAMIC ORGANIZATIONAL CULTURE,WORK ABILITY AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE IN ISLAMIC EDUCATION INSTITUTIONS - Raihanah Daulay; Efry Kurnia (Proceeding International Seminar of Islamic Studies, 2021)
Performance is the result of work produced by employees and companies. Employee performance will determine the success of the company. In order for performance to provide maximum results, many factors must be considered to influence it. Factors that can affect employee performance include organizational culture, work skills and emotional intelligence. This study aims to determine the effect of Islamic organizational culture, work ability and emotional intelligence on employee performance at the Islamic Education Institute in Medan. The population in this study were all employees of the Islamic Education Institute with a sample of 98 people. The data collection technique in this study used a questionnaire that was tested for validity and reliability and interviews. The data analysis technique in this study used the classical assumption test, multiple regression, t test, F test and the coefficient of determination The results showed, partially there is a significant influence of Islamic organizational culture on employee performance, there is a significant effect of work ability on employee performance, there is a significant effect of emotional intelligence on employee performance. Simultaneously there is an influence of Islamic organizational culture, work morale and emotional intelligence on employee performance at the Islamic Education Institute in Medan City.Keywords: Employee Performance, Islamic Organizational Culture, Work Ability, Emotional Intelligence